Evaluation of Atrioventricular Valve Regurgitation in Detection of Atrioventricular Septal Defects at First Trimester Ultrasound - Zhen Guo; Yang Yan; Yang Zhili; Xiao Juhua; Xiao Xiaojuan; Chen Jia; Luo Haiyan; Zhou Xin (International Journal of Clinical Practice)
Objective. To assess the effectiveness of atrioventricular valve regurgitation (AVVR) detection using color Doppler in the four-chamber view (4CV) for identifying atrioventricular septal defects (AVSDs) during 11–13 + 6 weeks’ gestation. This study compares AVVR detection to conventional 2D ultrasound and investigates associations between AVSD and increased nuchal translucency thickness (NT), as well as additional cardiac, extracardiac, and chromosomal abnormalities in the first trimester. Materials and Methods. This prospective study analyzed data from singleton pregnancies diagnosed with AVSD at 11–13 weeks gestation. It included routine ultrasound examinations focusing on fetal anatomy, NT measurement, and blood flow analysis across AVVR using both color and directional power Doppler. Evaluations targeted the 4CV and the three-vessel and trachea views (3VT). Ratios such as LAVV/RAVV and main pulmonary artery-to-aorta (PA/AO) diameter were also calculated. Results. Over three years, 452 fetuses were diagnosed with congenital heart disease in the first trimester, including 25 cases of AVSD (21 complete, 1 partial, and 3 intermediate). Seventeen cases were isolated AVSDs, 13 associated with heterotaxia syndrome, one with tetralogy of Fallot, and two survived. Among these, 92% showed AVVR, 61.54% had NT above the 95th percentile, and 32.0% lacked a nasal bone. AVVR was a more reliable indicator of AVSD than other ultrasonic markers. Conclusion. AVSD exhibits a diverse range of clinical presentations. A comprehensive review of both intracardiac and extracardiac anomalies is essential. AVVR detected during NT scanning in the first trimester can confirm the presence of AVSD.